Developing Puzzle Based Case Study to Improve Cognitive Learning Outcomes of High School Students - Sinta Kharomah; Deny Setiawan; Siti Zubaidah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
The aim of this research was to develop Puzzle Based Case Study (PBCS) media that is valid, practical, and effective in enhancing students' cognitive learning outcomes on the topic of the respiratory system. PBCS is a form of media that combines elements of a puzzle game with case study questions. The research followed the ADDIE development model, which includes the stages of Analyze, Design, Develop, Implement, and Evaluate. The validity of the media was determined through input from three validators: media experts, material experts, and educational practitioners. The practicality of the media was assessed through questionnaires administered to students and teachers. To measure the effectiveness of the media in improving cognitive learning outcomes, pretest and posttest assessments were conducted, followed by an analysis of the n-gain. The results of the material validation process showed a 100% agreement, while the media validation process also achieved a 100% agreement. The validation process involving educational practitioners resulted in a 98.6% agreement. The practicality of the media was rated as 95.6% (indicating high practicality). The effectiveness of the media, as measured by the N-Gain value of 0.62, met the criterion for effectiveness at 62% (moderately effective). These findings demonstrate that PBCS is a valid, practical, and effective tool for enhancing students' cognitive learning outcomes in the study of the respiratory system. Based on these results, PBCS can serve as a valuable resource for the development of other game-based media in various educational disciplines.